The Role of Digital Technologies in Capital Market Development: A Pathway to Economic Growth in Developing Countries - Edward Sandoyan; Dmitrii Rodionov; Mariam Voskanyan; Ani Galstyan (International Journal of Technology)
Digital technologies are important in developing capital markets in modern economic realities. Capital markets also have an essential role and weight in financial systems and can stimulate economic growth, investment, and savings in the country. Therefore, this research aimed to evaluate the causal relationship between market capitalization and economic growth in 27 developing countries, focusing on the role of regional integration and digitalisation. The hypothesis is that developing countries should focus on improving capital markets through regional integration and digitalization to stimulate economic growth. Quantitative data was used and based on the research results policy recommendations were developed. The research adopted a mixed method, including statistical and econometric analysis. The statistical analysis was carried out using graphical representations, deduction, and logical assumptions, while the econometric analysis was based on a panel data regression framework. The results showed that the weak development of the capital market due to poor digitalization in developing countries with small open economies had a significant negative effect on the investment environment and economic growth. Furthermore, a 10% increase in market capitalisation leads to a 1.8% and 0.21% increase in GDP and a 0.21% increase in GDP and FDI inflow, respectively. Recommendations on a complex institutional reform of the sector have been developed to eliminate possible obstacles to financial integration in the following directions, including institutional, legislative, and technical issues related to digital technologies. Implementation of public-private partnerships was also recommended as the best solution for overcoming financial barriers implementing digital technologies and developing capital markets in resource-constrained countries.